Community Policing, Workplace Structure and Attitudes Toward Lesbians and Gay Men and their Civil Liberties - Bernstein, Mary; Wulff, Stephen (International Journal of Criminology and Sociology, 2014)
While criminal justice workplaces, such as the police and prisons, are noted for reproducing both gender inequality and inequality based on sexuality or sexual orientation, this paper examines whether reorganizing the workplace can alter those interactions and reduce inequality. We draw on survey data from a police department to theorize the likely impact of the move toward community policing and rehabilitative models of justice on the attitudes of heterosexual sworn officers and civilian employees toward lesbians and gay men and their civil rights. Our analysis shows that sworn officers and civilian employees’ attitudes toward community policing and rehabilitation significantly affect their views on lesbians and gay men and their civil liberties both directly and indirectly. We conclude by suggesting the policy implications of our findings and avenues for future research.